Autism is a world [videorecording (DVD)] - Rubin, Sue; Margulies, Julianna, 1966- (CNN, 2004)
Sue Rubin, who is autistic, was diagnosed and treated as mentally retarded until the age of 13, when she began to communicate using a keyboard. She is now a junior in college. This documentary takes the viewer on a journey into her mind, her daily world, and her life with autism.